Pengaruh Kemampuan Kerja, Kompensasi, Disiplin Kerja dan Pengawasan terhadap Kinerja Karyawan Pada PT. PLN (Persero) UP3 Kota Metro - Sari, Peni Arum; Ratmono, Ratmono (Universitas Muhammadiyah Metro, 2021)
Employee performance is an important aspect in a company. The company strives to find and nurture employees with high enthusiasm, to create and maintain competitive human resources. Human resources are what ultimately become the backbone for the success of a company. The formulation of the problem in this study is